2022
DOI: 10.3390/app12020907
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Printed Chinese Character Recognition for ID Cards Using Deep Learning and Few Samples Transfer Learning

Abstract: In the field of computer vision, large-scale image classification tasks are both important and highly challenging. With the ongoing advances in deep learning and optical character recognition (OCR) technologies, neural networks designed to perform large-scale classification play an essential role in facilitating OCR systems. In this study, we developed an automatic OCR system designed to identify up to 13,070 large-scale printed Chinese characters by using deep learning neural networks and fine-tuning techniqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, using pixel accuracy alone may not be the most appreciated solution since in certain cases with high score values, some pixels may be wrongly classified. In (5) represents pixel accuracy (PA), with k + 1 classes, pij being the number of pixels of class i inferred to be of class j and pii are true positives. Binary cross entropy (BCE) is a loss function that is used to evaluate the performance of binary classification algorithms [20].…”
Section: Evaluation Metrics For Custom-built Text Detection Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using pixel accuracy alone may not be the most appreciated solution since in certain cases with high score values, some pixels may be wrongly classified. In (5) represents pixel accuracy (PA), with k + 1 classes, pij being the number of pixels of class i inferred to be of class j and pii are true positives. Binary cross entropy (BCE) is a loss function that is used to evaluate the performance of binary classification algorithms [20].…”
Section: Evaluation Metrics For Custom-built Text Detection Modelmentioning
confidence: 99%
“…Automating this process using the image of an identity card by traditional computing approaches is virtually impossible, as it requires an exact set of requirements to be respected regarding lighting conditions, orientation or background among others. With the increasing interest in deep learning and especially computer vision, few research works are applying deep learning techniques to retrieve text information from images including identity cards [2]- [5]. In computer vision, the field of study related to extracting and recognising text information from images is termed optical character recognition (OCR) [6].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, lots of research can be found on handwritten CR in these scripts, for instance [11]- [13] work on Chinese, Japanese (Kanji), and Korean (Hanja), respectively. The accuracy rates for the scripts based on the aforementioned references are 99.39%, 99.64%, and 86.9%, respectively.…”
Section: Logographic Systemmentioning
confidence: 99%
“…[48] English → online-handwritten → line level → public dataset → FC 5. [13] Chinese → offline-printed → character level → self-constructed dataset → PFC…”
Section: Examplesmentioning
confidence: 99%
“…In the case of handwritten documents, the content is created by a human; the uniformity of the space usage and the smoothness of the strokes influence the document's quality [6]. Another problem with handwritten papers is that some people simplify complex glyphs in the language script while writing them, which reduces inter-class diversity and increases intra-class variability [7]. Document aging and document digitization for processing may create many types of distortion in addition to problems in the paper used and defects that occurred during printing or writing.…”
Section: Introductionmentioning
confidence: 99%